Time-varying short-horizon predictability☆ - Henkel, Sam James; Martin, J. Spencer; Nardari, Federico (Journal of Financial Economics, 2011)
In the G7 countries, the short-horizon performance of aggregate return predictors such as the dividend yield and the short rate appears non-existent during business cycle expansions but sizable during contractions. This phenomenon appears related to countercyclical risk premiums as well as the time-variation in the dynamics of predictors. Our empirical model outperforms the historical average out-of-sample in the US, but the results throughout the G7 are mixed.